Pedestrians and cyclists interaction in urban settings of Pardubice city - Josef Bulíček (Psychology and its Contexts, 2014)
Presented paper is focused on questions of cyclist transport in urban settings, specifically in the city of Pardubice. Emphasis is put on analysis of potentially conflict places, especially in interaction with pedestrians. Direct terrain observation and consequent evaluation of conflict potential are used as method for data collecting. When cycling routes are designed, the requirements of the cyclists should be taken into account in order to ensure that the routes are accepted. In order to make planning user oriented one has to know which criteria are important for cyclists` route choice. Until now not many studies were conducted on this topic in Czech Republic. Theoretical background used states 5 basic requirements for cycle routes. These are: 1. Coherence (the cycling infrastructure forms a coherent unit and links with all departure points and destinations of cyclist), 2. Directness (the cycling infrastructure continually offers the cyclists as direct a route as possible, so detours are kept to a minimum, 3. attractiveness (the cycling infrastructure is designed and fitted to the surroundings in such a way that cycling is attractive), 4. safety (the cycling infrastructure guarantees the road safety of cyclists and other road users, 5. comfort (the cycling infrastructure enables a quick and comfortable flow of bicycle traffic.). Planners need a clear understanding of what influences bicycling behavior to develop effective strategies to increase use of those modes. Transportation practitioners have largely focused on infrastructure and the built environment, although researchers have found that attitudes are also very important. Theory of planned behavior (Ajzen, 1985) - intentions to perform behaviors of different kinds can be predicted with high accuracy from attitudes toward the behavior, subjective norms, and perceived behavioral control; and these intentions, together with perceptions of behavioral control, account for considerable variance in actual behavior. The theory of planned behavior (TPB) suggests that behavior such as active transportation results from a mixture of personal attitudes toward these modes, subjective norms, and a person's perceived behavioral control, giving us a way to conceptualize psychological factors that influence travel behavior. Furthermore, we work with Situational awareness (Endsley, 1999) - cognitive model of decision making based on perception of current situation, understanding of current situation and anticipation of future situation. Situational awareness influence decisions and future actions (the way we understand reality). The research results are indicating that cyclists prefer a track separated from flows of motor vehicles, in the case of presented research common space with pedestrians. Next results have shown disrespect of obligation to convey bike over pedestrian crossing by walking as well as mistaken using of cyclist crossings. Locations selected for research have got relatively high conflict potential on interaction with pedestrians. Proposed alternatives of possible solution are mentioned as a conclusion in two points of view - modification of infrastructure and information (education) of operation participants.